Intraductal fibroadenoma presenting with nipple bleeding in an adolescent: a case report and literature review - Gao, Pingfa; Yang, Wenyan; Guan, Wenbin; Wu, Ping; Lv, Wenjie (Frontiers in Pediatrics, 2025)
A 12-year-old Chinese adolescent girl presented with a 2-month history of left nipple bleeding. Physical examination revealed bloody and brownish nipple discharge. Ultrasonography identified a 1 mm solid mass within a dilated duct, and MRI showed heterogeneous enhancement. Surgical exploration revealed a well-defined, medium-textured mass within the duct, which was completely excised. Histopathological analysis confirmed an intraductal fibroadenoma with stromal infarction and hemorrhage, explaining the nipple discharge. Postoperatively, the patient recovered well without recurrence during a 12-month follow-up. Fibroadenoma, the most common benign breast lesion in adolescents, arises from estrogen-sensitive intralobular fibroblasts and may involve ductal structures, as in this case. Spontaneous infarction of intraductal fibroadenoma is exceptionally rare and can present with bloody discharge, necessitating differentiation from other intraductal lesions such as ductal adenoma and intraductal papilloma. This case highlights the importance of timely diagnosis and management of breast lesions in adolescents, emphasizing the need to distinguish between physiological changes and pathological conditions. The report also discusses the etiology of spontaneous infarction in intraductal fibroadenoma and its clinical implications, contributing to the understanding of this rare presentation in pediatric patients.